Strengthening of Fe60Co15Ni15Cr10 medium entropy alloy via heat-treatment-induced phase transformation and TiC reinforcement - Nagarjuna, Cheenepalli; Lee, Hansung; Dewangan, Sheetal Kumar; Song, Eunhyo; Mohan, Man; Jain, Reliance; Yu, Hwi Geun; Ahn, Byungmin (Journal of Alloys and Compounds, 2025)
The ferrous-rich Fe60Co15Ni15Cr10 medium entropy alloy (MEA) was prepared via mechanical alloying and spark plasma sintering. To further enhance the strength of the MEA, the present study developed two effective strategies: optimizing the heat treatment temperature and incorporating TiC nanoparticles as a reinforcement phase. The obtained results revealed the formation of a single-phase face-centered cubic (FCC) structure within the MEA powder after 30 h of milling. While the MEA/TiC composite powder exhibited both FCC and TiC phases. After sintering, the predominant FCC phase and a minor CrFe-rich body-centered cubic (BCC) phase were observed. However, as the heat treatment temperature increased, a fraction of the BCC phase significantly increased. Consequently, the hardness of MEA increased by 54 % after heat treatment at 900 °C, while its compressive yield strength (CYS) increased by 184 % after heat treatment at 1000 °C. The addition of 5 wt.% TiC reinforcement improved its hardness and CYS by 47 % and approximately 219 %, respectively. Furthermore, heat-treatment-induced microstructural heterogeneity provides multiple stages of strain hardening. Hence, this study demonstrates that heat-treatment-induced phase transformation and TiC reinforcement can significantly enhance the strength and hardness of MEA, providing a viable approach to developing high-performance, cost-effective alloys for structural applications.
Keywords: After-heat treatment; Body-centered-cubic phase; Heat treatment temperature; Induced phase transformation; Mechanical; Mechanical behavior; Medium entropy; Medium entropy alloy; Phases transformation; Spark-plasma-sintering; Mechanical behavior; Medium entropy alloy; Microstructure; Phase transformation; Reinforcement